Сравнительный анализ массостоимостных показателей асинхронных двигателей с цилиндрическим и аксиальным рабочим зазором - Ставинский, Андрей Андреевич; Пальчиков, Олег Олегович (НТУ "ХПИ", 2015)
На основе метода относительных коэффициентов показателей технического уровня с относительными геометрическими управляемыми переменными получены аналитические зависимости определения оптимальных геометрических соотношений по критериям минимума массы и стоимости активной части торцевых асинхронных короткозамкнутых двигателей и выполнен сравнительный анализ указанных показателей при традиционном и аксиальном исполнениях статора и ротора.

Purpose. To find the analytical expressions of determining the optimum geometric dimensions by criteria of the weight minimum and the cost minimum of axial field squirrel-cage induction motors and to compare traditional and axial field motors. Methodology. We have applied the adapted method of the relative indications of the technical level with relative controlled variables. We have used the approximation of the experimental dependence of the distribution of the induction in the air gap and the integral averaging of the electromagnetic characteristics. Results. We have developed the mathematical model for determining the optimum geometric dimensions by criteria of the weight minimum and the cost minimum of the active part of axial field squirrel-cage induction motors taking into account the radial distribution of the induction in the air gap and teeth. We have considered the comparative analysis of the indications of the weight and the cost of traditional and axial designs of electromagnetic equivalent motors.
Comparative analysis of weight and cost indications of induction motors with cylindrical and axial air gaps
Keywords: асинхронные двигатели; электродвигатели; электрические машины; асинхронный короткозамкнутый двигатель; показатели технического уровня; геометрические размеры; indications of the technical level; optimum geometric dimensions; traditional and axial field motors